2022
DOI: 10.1186/s12879-022-07342-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcome of viral acute lower respiratory infection in hospitalised children in Myanmar

Abstract: Background Acute lower respiratory infection (ALRI) remains the leading cause of death in children worldwide, and viruses have been the major cause of ALRI. In Myanmar, ALRI is associated with high morbidity and mortality in children, and detailed information on ALRI is currently lacking. Methods This prospective study investigated the viral aetiologies, clinical manifestations, and outcomes of ALRI in hospitalised children aged 1 month to 12 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…We investigated nasopharyngeal (NP) samples obtained from hospitalized children with ALRI who had participated in a prospective viral etiological study. Details of the study have been reported previously 10 . In brief, the study enrolled children with ALRI aged 1 month to 12 years who were admitted to Yankin Children Hospital (YKCH) in Yangon, Myanmar, during the period from April 2017 to March 2019.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated nasopharyngeal (NP) samples obtained from hospitalized children with ALRI who had participated in a prospective viral etiological study. Details of the study have been reported previously 10 . In brief, the study enrolled children with ALRI aged 1 month to 12 years who were admitted to Yankin Children Hospital (YKCH) in Yangon, Myanmar, during the period from April 2017 to March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…On admission, an NP swab was immediately placed in viral transport media and stored at −80°C in a freezer at YKCH and later transported to the laboratory of Niigata University, Japan, for viral analyses. The definition of ALRI and exclusion criteria for this study were also described in the previous report 10 . Briefly, ALRI was defined as (1) a fever of ≥38°C, (2) cough, (3) onset during the previous 10 days, and (4) need for hospitalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic analysis for the Global Burden of Disease Study 2016 estimated that there were 2,377,697 deaths due to LRTIs globally in 2016 [ 3 ]. Over the past decades, many countries have taken a range of actions to prevent and treat LRTIs, including the improvement of nutrition and hygiene, distribution and usage of influenza antibiotics and antivirals, and global promotion of Haemophilus influenzae type b and pneumococcal conjugate vaccines [ 4 , 5 ]. Despite remarkable progress has been made with these measures, LRTIs still bring huge burden to individuals and society.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many countries have taken a range of actions to prevent and treat LRTIs, including the improvement of nutrition and hygiene, distribution and usage of influenza antibiotics and antivirals, Yuting Chen and Jiran Shen contributed equally to this work and should be considered co-first author. and global promotion of Haemophilus influenzae type b and pneumococcal conjugate vaccines [4,5]. Despite remarkable progress has been made with these measures, LRTIs still bring huge burden to individuals and society.…”
Section: Introductionmentioning
confidence: 99%